Associations of obesity and novel lipid indicators in the risk of type 2 diabetes mellitus in Chinese elderly hypertensive patients - Jin, Xihui; Wei, Yushuang; Mo, YeMei; Zhang, Qiuling; Xu, Mingjie; Mai, Xiaoyou; Yan, Boteng; Xie, Wenchao; Huang, Shengzhu; Li, Mingli; Mo, Zengnan (Frontiers in Endocrinology, 2025)
BackgroundThe associations of waist circumference (WC), body mass index (BMI), lipid accumulation product (LAP), Chinese visceral adiposity index (CVAI), and triglyceride-glucose Index (TyG) with the risk of type 2 diabetes mellitus (T2DM) remained uncertain in Chinese middle-aged and elderly hypertensive patients.MethodsA total of 1,965 hypertensive participants aged 45 years and elderly were included in the cross-sectional analysis, and 1,576 hypertensive participants without T2DM for the cohort analysis. In the cross-sectional study, binary logistic regression, restricted cubic splines (RCS), and receiver operating characteristic (ROC) were used to analyze the relationships between WC, BMI, LAP, CVAI, and TyG with and T2DM in hypertensive patients. In the cohort study, Kaplan-Meier survival analyses and Cox regression were further performed to determine the associations of these indicators with incident T2DM risk.ResultsIn the cohort study, there were 101 incident T2DM cases occurred during a median follow-up of 30 months, with an incident rate was 2.78 per 100 person-years. The cross-sectional study showed that the risk of T2DM increased significantly with higher quartiles of WC, BMI, LAP, CVAI, and TyG (all P-trend < 0.001). In the cohort study, Cox regression model showed that WC (Q4 vs. Q1, HR = 3.30, 95% CI = 1.66-6.59), BMI (Q4 vs. Q1, HR = 2.38, 95% CI = 1.30-4.36), LAP (Q4 vs. Q1, HR = 5.15, 95% CI = 2.40-11.02), CVAI (Q4 vs. Q1, HR = 3.38, 95% CI = 1.76-6.50), and TyG (Q4 vs. Q1, HR = 5.76, 95% CI = 2.82-11.77) were associated with a higher risk of incident T2DM. RCS confirmed the positive dose-response relationships of WC, BMI, CVAI and TyG with T2DM in both study design, except for LAP in the cohort study. Additionally, ROC analysis revealed that TyG had the strongest area under the curve (AUC) of 0.70 (95% CI = 0.67-0.72) in the cross-sectional study, and the AUC of other indicators ranged from 0.55 to 0.57.ConclusionHigher levels of WC, BMI, LAP, CVAI, and TyG are associated with a higher riskof developing incident T2DM in Chinese elderly hypertensive patients, and TyG might be the most effective predictive indicator.